(untitled) (The Review of Diabetic Studies, 2024)
This study examines how well telemedicine services work to increase senior population satisfaction in remote parts of Saudi Arabia, improve clinical outcomes, and facilitate access to healthcare. The study aims to provide empirical proof of telemedicine’s impact on illness management, medication adherence, and ongoing situation monitoring for elderly patients through a quantitative evaluation of telemedicine treatments. The results show significant improvements in disease management scores, medication compliance costs, and ongoing condition monitoring metrics for senior citizens utilizing telemedicine services. The study also looks at how telemedicine can help older populations in remote areas receive better healthcare and experience fewer healthcare inequities. The study adds to the literature on telemedicine’s role in healthcare transportation by highlighting how it might overcome geographic constraints, enable prompt diagnosis and treatment, and improve healthcare outcomes for elderly people. The results of the observation highlight the significance of incorporating telemedicine into healthcare policies and plans to provide fair access to high-quality care for senior citizens living in remote places. All things considered, the study provides insightful information about how telemedicine might improve the quality of healthcare provided to elderly patients in Saudi Arabia and help them achieve better fitness levels.